Decoding pediatric spinal tumors: a single-center retrospective case series on etiology, presentation, therapeutic strategies, and outcomes - Lenga, Pavlina; Kühlwein, Daniel; Grutza, Martin; Issa, Mohammed; Hinz, Felix; Sahm, Felix; Selt, Florian; Milde, Till; Günther, Patrick; Unterberg, Andreas; Krieg, Sandro; El Damaty, Ahmed (Neurosurgical review, 2024)
Spinal tumors (ST) often result in dire prognosis, carrying risks such as permanent paralysis, sensory loss, and sphincter dysfunction. Data on their incidence and etiology in pediatric populations are markedly scant. Our study investigates the etiology, clinical manifestation, treatment, and outcomes of pediatric ST.